The Effect of Bio-Phophate Fertilizer at Lowlands on The Growth and Results of Cauliflower in Polybags - Rostian Nafery; Indrawani Sinoem; Nurlaila Safitri (International Journal of Social Service and Research (IJSSR), 2023)
This study aims to examine the Effect of Bio-Phosphate Fertilizer Application in the Lowlands on the Growth and Yield of Flower Cabbage (Brassica oleracea var. Botrytis L.) in Polybags. This research was carried out at SMK-PP Negeri Sembawa Kec. Sembawa, Banyuasin Regency, Palembang City, South Sumatra Province. This research was conducted from December 2020 to March 2021. The method used in this study was the experimental method (experiment), using a randomized block design (RBD) with 5 (five) treatments and 5 (five) groups/replications. Each experimental unit consisted of 10 plants so that the number of plants studied was 250 plants. Based on the research results, it can be concluded that the application of Bio-phosphate fertilizer has a good effect on the growth and yield of cauliflower (Brassica oleracea var. Botrytis L.) in polybags. The application of Bio Phosphate fertilizer had a good effect on the growth of plant height and number of leaves with a fertilizer dose of 15 g/polybag, the best plant height was 36.69 cm, and the number of leaves was 22.20. The application of Bio Phosphate fertilizer had a good effect on the yield of flower diameter, fresh weight of plants and fresh weight of flowers per plant with a fertilizer dose of 30 g/polybag obtained a flower diameter of 91.56 mm, plant fresh weight of 236.50 g and flower fresh weight per plant of 90.30 g.